Колекція кахель з Дубенського Спасо-Преображенського монастиря - Пшеничний, Ю.Л.; Ткач, В.В. (Археологія і давня історія України, 2018)
Стаття присвячена характеристиці та хронологічно-типологічному аналізу колекції пічних кахель зі Спасо-Преображенського монастиря міста Дубна XV—XVIII ст., виявлених під час археологічних досліджень в 1997—2017 рр. Investigations and new publications of the stove tiles collections allow more fully study regional culture of Ukrainian towns in the 15th—18th centuries. They give rich material for the characteristic of everyday life in influential centers like Spaso-Preobrazhensky monastery in Dubno. Because of archeological excavations the first chronologic group of tiles was distinguished. It had been used until the monastery was rebuilt from wooden to stone complex in the end of the 16th — the beginning of the 17th century. Till this time pot, basin and plate tiles had been used. The top chronologic line of using of tiles with renaissance topics can be correct till the first decades of the 17th century. Close analogies for the ornamental designs on the tiles are known in Polish, Lithuania and Byelorussia. The tiles with knight images testified a guardianship of monastery by the princes Ostrogsky. The identical tiles were used for the decoration of their castle. Craftsmen, who made tiles for the monastery, were doing the same for the castle and also to order of some rich citizens in close time. Their characteristic feature was some kind of mobility, which allows them personally or by mediation of others centers adopt popular styles of that time in Polish and Lithuania.